An act additional to "An act respecting mortgages and the rights in equity of redemption." (Document (Maine. Legislature. Senate), 1838)
1838 Senate bill amending an act regarding mortgages and the rights in equity of redemption by also allowing public notice in newspapers on pending foreclosures.